IMPROVEMENT OF LEARNING OUTCOMES AND CONCEPTUAL UNDERSTANDING OF GRADE V STUDENTS THROUGH THE USE OF A PROBLEM-BASED LEARNING MODEL ASSISTED BY REALIA MEDIA - Rahmi, Putri; Oviana, Wati; Jannah, Misbahul; Hayati, Zikra; Uswanti, Dini (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
In the process of implementing science learning in class V at MIN 2 Nagan Raya, it is still dominated by students who are not able to understand the material well, this is evidenced by the data of student learning observation is still below the KKM, which is 60. The objectives of this study are: (1) to analyze teacher activities, (2) to analyze student activities, (3) to analyze the improvement of concept understanding, (4) to analyze learning outcomes after applying the Problem Based Learning model assisted by realia media in class V MIN 2 Nagan Raya. The method used in this study is Classroom Action Research (PTK). The data collection techniques used are observation and Test, data analysis techniques used using a percentage formula. The results of the study showed that (1) the activity of teachers in the first cycle obtained a percentage of 82.40% in the second cycle increased with a percentage of 92.59%. (2) Student activity in the first cycle obtained a percentage of 78.70%, increased in the second cycle with a percentage of 89.81%, (3) The results of the concept comprehension test of students in the first cycle were 63.23% and then increased in the second cycle with a percentage of 86.97%, (4) the learning outcomes of students in the first cycle were 52.94% and increased in the second cycle to 92.85%. Thus, it can be concluded that there is an increase in students' understanding of concepts and learning outcomes through the use of the Problem Based Learning model assisted by Realia media in class V MIN 2 Nagan Raya.Keywords: Conceptual Understanding, Problem Based Learning, Realia Media